Archaeological Investigations Into the Origins of Bel Trading Groups Around the Madang Coast, Northeast New Guinea. (2nd October 2018) - Gaffney, Dylan; Summerhayes, Glenn R.; Mennis, Mary; Beni, Teppsy; Cook, Affrica; Field, Judith; Jacobsen, Geraldine; Allen, Fran; Buckley, Hallie; Mandui, Herman
ABSTRACT: This article presents archaeological data critical to our understanding of the pre-colonial past along the northeast coast of New Guinea. Two archaeological sites from coastal and offshore Madang, Papua New Guinea, were excavated to establish the timing of colonization by Bel (Austronesian) speakers, and the subsequent emergence of their trade and exchange networks along the coast leading up to ethnographic accounts. These sites include Nunguri on Bilbil Island, formerly the center of the expansive Madang (Bilbil) pottery exchange network, and Tilu, Malmal village, a pottery consumption area along the coast. Both excavations suggest that initial occupation at these sites by the Bel-speaking groups occurred very recently in the last millennium before present (c. 550–650 cal BP), which is broadly in line with oral history and linguistic evidence. From the start, this occupation involved local red-slipped pottery production and distribution, the exchange of obsidian and sedimentary lithics, and the consumption of nearshore marine resources along with key domesticated animals. In-depth descriptions of these investigations and the archaeological material are presented here.